Proposal: The Location for Installation of Digital Signage at KAED Gallery - Ayob, Mohd Fairullazi (2015)
The IIUM Rector has agreed with the Malaysian Prime Minister’s Office request on the installation of digital signage under the Federal Government Indoor Digital Media project.